2019
DOI: 10.32615/ps.2019.115
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation mechanism of ozone-induced reduction in net photosynthesis of Bangladeshi wheat under soil salinity stress

Abstract: To clarify the combined effects of O3 and soil salinity on net photosynthetic rate, stomatal conductance, and radical scavenging system of Bangladeshi spring wheat cv. BAW1059, plants were grown in two soil salinity levels (irrigated with 0 and 150 mM NaCl solutions) and exposed to three O3 concentrations [charcoal-filtered air (CF), 1.0-fold the ambient O3 concentration (1.0×O3), and 1.5-fold the ambient O3 concentration (1.5×O3)]. The soil salinity mitigated adverse effects of O3 on net photosynthesis in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The authors concluded that O 3 tolerance improved at different growth stages via regulating antioxidant activities in tolerant cultivars. In another study, O 3 exposure-induced ROS production was scavenged via regulation of antioxidant activities in wheat leaves [ 298 ].…”
Section: Antioxidant Metabolism and The Detoxification Of Ros Undementioning
confidence: 99%
“…The authors concluded that O 3 tolerance improved at different growth stages via regulating antioxidant activities in tolerant cultivars. In another study, O 3 exposure-induced ROS production was scavenged via regulation of antioxidant activities in wheat leaves [ 298 ].…”
Section: Antioxidant Metabolism and The Detoxification Of Ros Undementioning
confidence: 99%
“…Increasing soil CaCO 3 by the experimental treatments can be due to the enhanced colloidal properties of the soil such as the availably of SOC and nutrients and the improved structure of the soil such as the stability of aggregates. Increasing ozone concentration increased CaCO 3 , which can be due to a more favorite soil medium by affecting soil physical, chemical, and biological properties [ 21 , 31 ].…”
Section: Discussionmentioning
confidence: 99%